2021
DOI: 10.52562/jdle.v1i01.31
|View full text |Cite
|
Sign up to set email alerts
|

Partisipasi Orang Tua Terhadap Pembelajaran Online di Rumah Ditinjau Dari Fase Kelas di Sekolah Dasar

Abstract: Abstrak: Penelitian ini bertujuan untuk (1) mengetahui bagaimana partisipasi orang tua dalam mendukung kegiatan pembelajaran online pada siswa dan (2) mengetahui apakah terdapat perbedaan partisipasi yang orang tua berikan pada siswa kelas tinggi dan kelas rendah. Penelitian ini merupakan penelitian kuantitatif dengan metode survei. Jumlah subjek dalam penelitian ini yaitu 60 orang tua siswa dari kelas I-VI SD Negeri 1 Seren. Teknik pengambilan sampel dalam penelitian ini adalah probability sampling dengan tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Based on the results of interviews with some elementary school teachers, online learning makes learning objectives not fully conveyed to students, and the teachers themselves still do not understand the use of the latest technology (Anggianita et al, 2020;Mailizar et al, 2020). In addition, the factor of the level of parental participation in online learning is still low (Huda, 2020;Khasanah et al, 2021). These existing obstacles are a challenge in the implementation of online learning considering that online implementation is a must so that educational activities can be conducted during the covid-19 pandemic (Arifa, 2020;Onyema, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of interviews with some elementary school teachers, online learning makes learning objectives not fully conveyed to students, and the teachers themselves still do not understand the use of the latest technology (Anggianita et al, 2020;Mailizar et al, 2020). In addition, the factor of the level of parental participation in online learning is still low (Huda, 2020;Khasanah et al, 2021). These existing obstacles are a challenge in the implementation of online learning considering that online implementation is a must so that educational activities can be conducted during the covid-19 pandemic (Arifa, 2020;Onyema, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of online teaching and learning experiences many obstacles, both from students and from teachers as facilitators. Findings from research on students' perceptions of online learning found that many of the students had difficulties because there was no direct interaction with the teacher so the material presented could not be conveyed optimally (Bestiantono et al, 2020;Khasanah et al, 2021). Lack of internet access and inadequate technology are also obstacles to the online learning process.…”
Section: Introductionmentioning
confidence: 99%